Legal regulation of commercial rights in international air law - Жмур, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In the article analyzes problem of legal regulation of commercial rights in international air law. Analyzed normatively-legal acts of rights, which have been given from one country to another, under which appointed carriers have rights to carry out transportation of passengers, luggage and freight by established international air routes according to reciprocal contract about air connection.